PERANAN KEPALA SEKOLAH SEBAGAI SUPERVISIOR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN (Telaah Teortik) - Rustam Hasim; Subhan Hayun (Universitas Khairun, 2018)
Principal as a supervisor has important roles in learning and teaching process, and has educational standards and qualities. In performing his or her roles, principal always pays attention to human relations among teachers, employers and students. Supervision is an effort to help and service teachers to improve their teaching ability. Supervisor is not directly linked to students, since teachers manage students. Supervisor is not a directive task but more likely to be a consultative one (such as supporting, suggesting, and guiding). Method used in this research is descriptive qualitative method which illustrates and describes the roles of principal in improving the learning quality. The roles of principal as administrator and supervisor are the main object. Based on teacher competency, the ability of teachers shows a slight improvement. The improvement of teachers' ability is resulted from supervision ways and approaches at school in managing, supporting and guiding the elements of schools. Based on quality standard, the implementation of supervision is improved. This means that the assistance and the management of the supervisor of the principal, and supervision approaches implemented by the principal in his or her effort to increase and to develop teachers' competency in the process of learning and teaching show better qualities and progression.Keywords: Supervision, Principal, and Teachers' Competency